Suicidal Ideation in Adult Patients with Atopic Dermatitis: A German Cross-sectional Study - Jan Dieris-Hirche; Uwe Gieler; Frank Petrak; Wolfgang Milch; Bert te Wildt; Barbara Dieris; Stephan Herpertz (Medical Journals Sweden, 2017)
A cross-sectional study was performed to assess symptoms of suicidality, depression and anxiety in adult patients with atopic dermatitis. The study describes the relationships between these psychiatric symptoms and skin-specific factors, such as atopic dermatitis severity and skin satisfaction. A sample of 181 German patients with atopic dermatitis was compared with a control group of 64 persons with healthy skin with a similar age and sex distribution. Standardized questionnaires were used to assess suicidality (Pöldinger's Scale), depression and anxiety (Hospital Anxiety and Depression Scale; HADS), quality of life (Dermatology Life Quality Index; DLQI), atopic dermatitis severity (Patient-Oriented Scoring Atopic Dermatitis; PO-SCORAD) and skin satisfaction (Skin Satisfaction Questionnaire; SSQ). The prevalence of suicidal ideation among patients with atopic dermatitis was high (21.3%); 3.9% scored above the cut-off that might be an indicator for acute suicidality. Depression symptoms, high severity of atopic dermatitis, lower age, and little touching within the family were identified as significant factors to predict suicidality in atopic dermatitis. Psychiatric screening in dermatological treatment of atopic dermatitis is discussed.